Mechanisms of skeletal muscle aging: insights from Drosophila and mammalian models - Fabio Demontis; Rosanna Piccirillo; Alfred L. Goldberg; Norbert Perrimon (The Company of Biologists, 2013)
A characteristic feature of aged humans and other mammals is the debilitating, progressive loss of skeletal muscle function and mass that is known as sarcopenia. Age-related muscle dysfunction occurs to an even greater extent during the relatively short lifespan of the fruit fly Drosophila melanogaster. Studies in model organisms indicate that sarcopenia is driven by a combination of muscle tissue extrinsic and intrinsic factors, and that it fundamentally differs from the rapid atrophy of muscles observed following disuse and fasting. Extrinsic changes in innervation, stem cell function and endocrine regulation of muscle homeostasis contribute to muscle aging. In addition, organelle dysfunction and compromised protein homeostasis are among the primary intrinsic causes. Some of these age-related changes can in turn contribute to the induction of compensatory stress responses that have a protective role during muscle aging. In this Review, we outline how studies in Drosophila and mammalian model organisms can each provide distinct advantages to facilitate the understanding of this complex multifactorial condition and how they can be used to identify suitable therapies.